Changes in plasma arginine vasopressin concentrations in cyclists participating in a 109-km cycle race. Issue 8 (15th July 2008) - Hew-Butler, T; Dugas, J P; Noakes, T D; Verbalis, J G
Abstract : Objective: To evaluate the osmotic and non-osmotic regulation of arginine vasopressin (AVP) during endurance cycling. Design: Observational study. Setting: 109 km cycle race. Participants: 33 Cyclists. Interventions: None. Main outcome measurements: Plasma sodium concentration ([Na + ]), plasma volume (PV) and plasma arginine vasopressin (AVP) concentration ([AVP]p ). Results: A fourfold increase in [AVP]p occurred despite a 2-mmol l −1 decrease in plasma [Na + ] combined with only modest (5%) PV contraction. A significant inverse correlation was noted between [AVP]p Δ and urine osmolality Δ (r = −0.41, p<0.05), whereas non-significant inverse correlations were noted between [AVP]p and both plasma [Na + ] Δ and % PV Δ. Four cyclists finished the race with asymptomatic hyponatraemia. The only significant difference between the entire cohort with this subset of athletes was postrace plasma [Na + ] (137.7 vs 133.5 mmol l −1, p<0.001) and plasma [Na + ] Δ (−1.9 vs −5.1 mmol l −1, p<0.05). The mean prerace [AVP]p of these four cyclists was just below the minimum detectable limit (0.3 pg ml −1 ) and increased marginally (0.4 pg ml −1 ) despite the decline in plasma [Na + ]. Conclusions: The osmotic regulation of [AVP]p during competitive cycling was overshadowed by non-osmotic AVP secretion. The modest decrease in PV was not the primary non-osmotic stimulus to AVP. Partial suppression of AVP occurred in four (12%) cyclists who developed hyponatraemia during 5 h of riding. Therefore, these results confirm that non-osmotic AVP secretion and exercise-associated hyponatraemia does, in fact, occur in cyclists participating in a 109 km cycle race. However, the stimuli to AVP is likely different between cycling and running.